Advances in non-enzymatic glucose sensors based on metal oxides - Zhu, H.; Li, L.; Zhou, W.; Shao, Zongping; Chen, X. (R S C Publications, 2016)
© The Royal Society of Chemistry.Glucose sensors have been extensively developed because of their broad applications, especially in diabetes diagnosis. Up to date, electrochemical enzymatic glucose sensors are commonly used in daily life for glucose detection and commercially successful as glucose-meters because they exhibit excellent selectivity, high reliability, and could be handled under physiological pH conditions. However, considering some intrinsic disadvantages of enzymes, such as high fabrication cost and poor stability, non-enzymatic glucose sensors have attracted increasing research interest in recent years due to their low cost, high stability, prompt response, and low detection limit. Furthermore, the development of nanotechnology has also offered new opportunities to construct nanostructured electrodes for glucose sensing applications. With distinguished advantages, metal oxides have garnered extensive effort in the development of cost-effective sensors with high stability, sensitivity and quick response for the determination of glucose via electrochemical oxidation. Hence, this review summarizes the advances in non-enzymatic glucose sensors based on different metal oxides (such as ZnO, CuO/Cu2O, NiO, Co3O4, MnO2, etc.) and their nanocomposites. Additionally, a brief prospective is presented on metal oxides for glucose sensors.